(untitled) (Vietnam Journal of Community Medicine, 2020)
Acute respiratory infections currently have high morbidity and mortality rates, are the leading cause of the burden of disease and the 3rd leading cause of death in children under 5 years old. The care, management and prevention of acute respiratory infections not only depend on health workers, but also on mother’s knowledge. Mothers have good knowledge about diseases, care plays an important role in disease prevention, early detection and timely delivery of children to health facilities, helping to reduce the infant morbidity and mortality rate. From that fact, the study was conducted to describe the current state of knowledge of mothers with children under 5 years old infected with acute respiratory infections in Thai Binh Hospital for Children in 2020. The research results show that the mother’s general knowledge about diseases, care and prevention of ARI is still limited with the average score of knowledge of the intervention group is 22.0 ± 7.0 and the control group is 22, 5 ± 6.5 (maximum of 44 points). Average points of knowledge about disease, care and prevention, respectively: 12.0 ± 4.3; 4.9 ± 2.1; 5.1 ± 1.8 in the intervention group and 12.4 ± 4.2, 5.0 ± 1.8, 5.0 ± 1.9 in the control group. The proportion of mothers with knowledge of both groups was low: 20.0% in the intervention group and 21.7% in the control group. Therefore, it is very necessary to strengthen health education for mothers of health workers, especially nursing staff.